A high efficiency C-band internally-matched harmonic tuning GaN power amplifier. (September 2016) - Lu, Y.; Zhao, B.C.; Zheng, J.X.; Zhang, H.S.; Zheng, X.F.; Ma, X.H.; Hao, Y.; Ma, P.J.
Graphical abstract: Highlights: A C-band gallium nitride (GaN) internally-matched power amplifier (PA) with 72.1% PAE and 107.4 W output power is presented. Harmonic manipulation circuits for high efficiency matching are induced both in the input and output matching networks. 1000 hours' aging test reveals high reliability for practical applications. Abstract: In this paper, a high efficiency C-band gallium nitride (GaN) internally-matched power amplifier (PA) is presented. This amplifier consists of 2-chips of self-developed GaN high-electron mobility transistors (HEMTs) with 16 mm total gate width on SiC substrate. New harmonic manipulation circuits are induced both in the input and output matching networks for high efficiency matching at fundamental and 2nd-harmonic frequency, respectively. The developed amplifier has achieved 72.1% power added efficiency (PAE) with 107.4 W output power at 5 GHz. To the best of our knowledge, this amplifier exhibits the highest PAE in C-band GaN HEMT amplifiers with over 100 W output power. Additionally, 1000 hours' aging test reveals high reliability for practical applications.